Squamous Cell Carcinoma of the Esophagus Can Be Detected by Microsatellite Analysis in Tumor and Serum - EISENBERGER, Claus F; KNOEFEL, Wolfram T; PEIPER, Matthias; MERKERT, Petra; YEKEBAS, Emre F; SCHEUNEMANN, Peter; STEFFANI, Katharina; STOECKLEIN, Nikolas H; HOSCH, Stefan B; IZBICKI, Jakob R (Clinical cancer research, 2003)
Purpose: Esophageal squamous cell cancer can be treated effectively by potentially curative surgery if diagnosed at an early stage. Our aim was to develop a novel molecular approach as a noninvasive test for squamous cell cancer detection and as an indicator for the prognosis of the patients. Experimental Design: Matched normal, tumor, and serum samples were obtained from 28 patients with squamous cell carcinoma (SCC) of the esophagus. DNA was extracted, and the samples were subjected to microsatellite analysis using 12 markers. Serum and normal DNA from 10 healthy individuals served as controls. Results: Twenty-six of the 28 patients (92.9%) with SCC were found to have one or more microsatellite DNA alterations in their primary tumor. Twenty-seven of the 28 patients (96.4%) had at least one alteration in the serum by microsatellite analysis. Mean age was 61.5 years. Microsatellite alterations were not identified in the serum DNA of samples from normal control subjects. Median follow-up was 13 months. Survival and recurrence were not significantly correlated with either loss of heterozygosity in the tumor or in the serum. Conclusions: Microsatellite DNA analysis of tumor and serum specimen is a potentially valuable tool for detection and for the evaluation of the prognosis of SCC of the esophagus. The follow-up in our study is still too short to draw final conclusions on the correlation of disease-specific survival and disease recurrence with microsatellite alterations. The evidence of circulating tumor DNA in almost all of our patients underlines a systemic component of the disease that is not surgically amenable.